The Effect of Traditional Thai Massage on Quality of Sleep in Adults with Sleep Problem - Chompoopan, Warangkana; Eungpinichpong, Wichai; Chompoopan, Worawut; Sujimongkol, Chinakorn (Trends in Sciences, 2022)
Sleep problem or insomnia is one of the most common causes of health problems, affecting around 10 - 20 % of the world population. Traditional Thai massage (TTM) is a popular alternative treatment in Thailand for reducing fatigue and improving sleep quality. This study aimed to examine the effect of traditional Thai massage on sleep quality in adults. Twenty-eight adults with poor sleep quality (based on Verran and Snyder-Halpern sleep scale) participated. They were randomly allocated into a control group (n = 14) and a TTM group (n = 14). Participants in the TTM group received three 90-min whole body traditional Thai massage sessions within one week, whereas the control group participants maintained their daily lives. Quality of sleep was assessed before and a day after the massage sessions. The outcome measure was the Verran and Snyder-Halpern sleep scale. The within-group data was analyzed by Paired t-test, whereas ANCOVA did the between-group data. The results showed that the participants in the TTM group had significantly decreased score of sleep disturbance (31.63 ± 2.95 vs 45.47 ± 3.24, p < 0.001) and increased the effectiveness score (70.73 ± 7.33 vs 53.47 ± 4.23, p < 0.001) after the last session of massage as compared to those of the control group. We conclude that TTM could significantly improve sleep quality without any adverse effects. HIGHLIGHTS The overall prevalence of insomnia in Thai adults was 40.8 % and is commonly found in the Thai population Sleep quality was associated with all the academic performance in adolescents and cognitive function in adults Traditional Thai massage could significantly improve sleep quality without any adverse effects Since this treatment is generally safe and comfortable, it could be used as an alternative therapy to treat people with sleep problems GRAPHICAL ABSTRACT